Corporate transparency and the disposition effect - Chen, Siliu; Ren, Fei (Frontiers in Psychology, 2025)
The disposition effect describes investors’ irrational behavior of selling profitable assets too soon while holding onto losing assets for too long. This study examines the impact of transparency at the firm level on the disposition effect of individual investors who hold that company’s stock. Our results show that an increase in corporate transparency significantly reduces the disposition effect. Further analysis reveals that for companies with greater transparency, individual investors tend to hold the company’s stock for a longer period rather than trade frequently. This behavior reduces the probability of investors selling the company’s stock. When the position in the stock is profitable, the probability of selling it decreases much more than when the stock is held at a loss, thus overall reducing the disposition effect.